2020
DOI: 10.1002/adom.201901390
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Formamidinium Lead Bromide Perovskite Nanocrystal‐Based Light‐Emitting Diodes Fabricated via a Surface Defect Self‐Passivation Strategy

Abstract: Formamidinium lead bromide (FAPbBr3) nanocrystals (NCs) demonstrate great potential in light‐emitting diode (LED) applications due to their pure green emission and excellent stability. However, the abundant defects at the surface of the NCs act as charge trapping centers and significantly increase the trap‐assisted nonradiative recombination channels, hampering the performance improvement of LEDs based on FAPbBr3 NCs. Herein, a facile self‐passivation strategy of the surface defects is developed by introducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 52 publications
3
58
0
Order By: Relevance
“…By contrast with perovskite photovoltaic devices that generally have stoichiometric precursors, the fabrication of PeLEDs typically uses excess halide salts (AX) to passivate defects, [59][60][61] modulate film crystallization (decrease crystallite size, [62,63] eliminate the non-perovskite δ-phase, [64] and create island morphology beneficial for light out-coupling [65,66] ), tune band alignment, [67] and balance charge injection [1] and prevent leakage current. [65,66] In our previous work, we demonstrated that after the film formation, excess FAI derived from perovskite precursors still exist at grain boundaries and in the gaps between island grains (Figure 2c).…”
Section: Excess Ions From Precursorsmentioning
confidence: 99%
“…By contrast with perovskite photovoltaic devices that generally have stoichiometric precursors, the fabrication of PeLEDs typically uses excess halide salts (AX) to passivate defects, [59][60][61] modulate film crystallization (decrease crystallite size, [62,63] eliminate the non-perovskite δ-phase, [64] and create island morphology beneficial for light out-coupling [65,66] ), tune band alignment, [67] and balance charge injection [1] and prevent leakage current. [65,66] In our previous work, we demonstrated that after the film formation, excess FAI derived from perovskite precursors still exist at grain boundaries and in the gaps between island grains (Figure 2c).…”
Section: Excess Ions From Precursorsmentioning
confidence: 99%
“…5–10 Light emitting diodes and solar cells based on these metal halide perovskites have shown excellent performance with efficiencies of nearly 25% power conversion efficiency (PCE) of solar cells and 20% external quantum efficiency (EQE) of LEDs. 4,11–19 However, these families of perovskites contain Pb which limits the commercial viability of these materials due to its environmental incompatibility and toxicity. 17 The subsequent development of Pb-free perovskite systems has been extensive; however, the performance of these materials is inferior to their Pb-containing analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after this paper, there followed several other LARP syntheses of MAPbX 3 and FAPbX 3 NCs, following similar protocols. [49][50][51][52] However, the thermal and environmental stability of these materials are compromised by their volatile organic cations. [53,54] All-inorganic CsPbX 3 typically offers much higher stability, and therefore represents a far more realistic option for commercial applications.…”
Section: Organic-inorganic Perovskite Nanocrystalsmentioning
confidence: 99%